On the Local Regularity of Solutions for Double Degenerate Nonlinear Parabolic Equations (uq-1)t=div(|ΔU|p-2ΔU) When 1 (Journal of Partial Differential Equations, 1993)
In this paper, we establish interior Hölder estimates of solutions for double degenerate nonlinear parabolic equations (u^{q-1})_t = div (|∇u|^{p-2}∇u) when 1 < p < 2, p ≤ q.
Keywords: Hölder continuity; double degenerate; nonlinear parabolic equations